L'Extension des Theories de l'Equilibre Economique General et du Rendement Social au Cas du Risque - Allais, M. (Econometrica, 1953)
following study proposes to generalize the classical theory of economic equilibrium and of welfare economics to the case of risk. Besides our own work, the only similar attempt which has been made in this field is, to the best of our knowledge, Mr. Arrow's paper, The Role of Securities in the Optimal Allocation of Risk-Bearing, presented at the international colloquium on risk which was held in Paris, May, 1952. It is quite astonishing that such an important chapter of economics, both from theoretical and practical points of view, has up to now never been the object of systematic study. reason for this is certainly its great difficulty. As the method of attacking this problem is doubtless the basic difficulty, we have, in order to make the exposition easier, confined ourselves to a simplified model. This has the double advantage of making perfectly evident the main considerations which, in our opinion, must enter into the analysis and of providing a simple and explicit framework for discussion. This model, furthermore, lends itself to easy generalization. Generally it can be said that the essential results of the theories of economic equilibrium and welfare economics are still valid in the case of risk.